2017
DOI: 10.1021/acs.cgd.7b00259
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Crystallization Kinetics of Supercooled Liquid GeTe by Ultrafast Calorimetry

Abstract: Crystallization kinetics of phase change materials (PCMs) at high temperatures is of key importance for the extreme speed of data writing and erasing. In this work, the crystallization behavior of one of the typical PCMs, GeTe, has been studied using ultrafast differential scanning calorimetry (DSC) at high heating rates up to 4 × 104 K s–1. A strong non-Arrhenius temperature-dependent viscosity has been observed. We considered two viscosity models for estimating the crystal growth kinetics coefficient (U kin)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 42 publications
4
52
1
Order By: Relevance
“…However, on the basis of the ultrafast DSC, Orava et al reported that m is ∼90 for GST, 2) and our previous study showed m of GeTe of ∼130. 27) Apparently, the present results of the fragility of PCMs are different from the previous ones. It may due to the fragile-to-strong transitions present in such Te-based supercooled liquids.…”
Section: −1contrasting
confidence: 98%
“…However, on the basis of the ultrafast DSC, Orava et al reported that m is ∼90 for GST, 2) and our previous study showed m of GeTe of ∼130. 27) Apparently, the present results of the fragility of PCMs are different from the previous ones. It may due to the fragile-to-strong transitions present in such Te-based supercooled liquids.…”
Section: −1contrasting
confidence: 98%
“…%). Liquid GeTe was reported to be a high-fragility liquid with m ≈ 131 inferred from ultrafast differential scanning calorimetry (FDSC) [10], or m ≈ 104-111 by molecular-dynamic (MD) simulations [8]. Such a high fragility does not conform well to the relatively lower activation energy for crystal growth Q G = 171 kJ mol −1 [11] reported for GeTe in contrast to the value of Q G = 227 kJ mol −1 for GST [12].…”
Section: Introductionmentioning
confidence: 91%
“…This was also emphasized recently by Orava and Angell, they claimed the unreliable threshold of the heating rate is 10 000 K/s for the phase‐change material Ge 2 Sb 2 Te 5 . Figure shows the Johnson‐Mehl‐Avrami (JMA) numerical simulated DSC peaks with heating rates from 5 to 600 K/min (the JMA simulation is similar to previous works and the details are not shown here) and the corresponding crystallized fraction of GGS and GGS‐Au. We found that, there is only a very insignificant difference between T p and T 0.63 in GGS and GGS‐Au when the heating rate is 60 K/min, that is, being about 2 and 2.5 K, respectively.…”
Section: Resultsmentioning
confidence: 85%
“…On basis of the Stokes‐Einstein relation between U kin and viscosity η , for example, U kin ∝ η −1 , we can deduced the expression of U kin as,log10Ukin=C-log10ηwhere C is a constant to indicate the difference between U kin and η −1 . In this work, we use MYEGA viscosity model to describe the temperature‐dependent viscosity η of supercooled liquid GGS and GGS‐Au.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation